Currency Hedging for International Portfolios - GLEN, JACK; JORION, PHILIPPE (Journal of Finance, 1993)
ABSTRACT This paper examines the benefits from currency hedging, both for speculative and risk minimization motives, in international bond and equity portfolios. The risk‐return performances of globally diversified portfolios are compared with and without forward contracts. Over the period 1974 to 1990, inclusion of forward contracts results in statistically significant improvements in the performance of unconditional portfolios containing bonds. Conditional strategies are also implemented, both in sample and out of sample, and are shown to both significantly improve the risk‐return tradeoff of global portfolios and to outperform unconditional hedging strategies.